2015
DOI: 10.1007/s11408-015-0251-7
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of demand and supply in the Euro interbank market: the role of “Key Players” during the recent turmoil

Abstract: We study frictions in trading patterns in the Euro money market. We characterize the structure of lending relations during the period of recent financial turmoil. We use a network-topology method on data from overnight transactions in the Electronic Market for Interbank Deposits (e-MID) to investigate two main issues. First, we characterize the roles of borrowers and lenders in long-run relationships by providing evidence on network formation at a 3-month frequency. Second, we identify the "key players" in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…In two other studies on the Italian IMM data, both Liberati et al. (2015) and Temizsoy et al. (2015) found that although relationship lenders played an essential role as liquidity providers, especially amid the global financial crisis of 2007−2008, they nevertheless forced borrowers to pay premiums for transactions.…”
Section: Results Of Integrative Review: the Affecting Factorsmentioning
confidence: 98%
See 3 more Smart Citations
“…In two other studies on the Italian IMM data, both Liberati et al. (2015) and Temizsoy et al. (2015) found that although relationship lenders played an essential role as liquidity providers, especially amid the global financial crisis of 2007−2008, they nevertheless forced borrowers to pay premiums for transactions.…”
Section: Results Of Integrative Review: the Affecting Factorsmentioning
confidence: 98%
“…They confirmed that the trustworthy relationships relatively increase during crisis periods, while some of the untrustworthy ones disappear. In two other studies on the Italian IMM data, both Liberati et al (2015) and Temizsoy et al (2015) found that although relationship lenders played an essential role as liquidity providers, especially amid the global financial crisis of 2007−2008, they nevertheless forced borrowers to pay premiums for transactions. A recent study on the Italian interbank network by Kobayashi and Takaguchi (2018) confirmed that relationship lenders tend to impose higher interest rates on borrowers in times of financial distress.…”
Section: Shock and Crisismentioning
confidence: 98%
See 2 more Smart Citations
“…Even if the banks do not participate in the interbank market on their own but via a central institution, the ability of the central institution to transmit funds to smaller banks is hampered Liberati et al (2015). shows that key players in the European interbank market exert their market power in times of disruption on the interbank market.…”
mentioning
confidence: 99%